Developing English Materials Using ESP Approach for al-Qur’an and Tafsir Study Program Students - Nurliana, Nurliana (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
This study aimed at developing English materials using ESP approach for the first semester students of al-Qur’an and Tafsir Study Program at IAIN Palangka Raya in academic year 2018/2019. In this study, the model of materials development proposed by Sugiyono (2013:298) was adapted with the following steps: need assessment, reference of the research, development of English materials using ESP approach, expert validation, revision, try-out of the materials, revision, and final product. The instruments used consisted of questionnaire, observation, and interview. The data gathered was analyzed and described qualitatively. The students’ need based on the result of questionnaire was English materials using ESP approach. Considering that result, the English materials using ESP approach were developed and tried in 8 meetings. The data collected from try-out showed that the developed materials were applicable to the teaching-learning process and appropriate with the students’ need. Furthermore, the students responded positively toward the developed materials. They were active, motivated, and enthusiastic in doing the activities of the developed materials. English materials using ESP approach in the form of a textbook divided into eight units were the product of this study. The topics were Prayer, Fasting, Zakat, Muamalat, Food in Islamic Law, Property Right in Islamic Law, Inheritance in Islamic Law, and al-Qur’an and Science. The textbook was also supplemented with a list of vocabularies section, a list of regular verbs section, and a list of irregular verbs section.